A "influência" do mito babilônico da criação, enuma elish, em Gênesis, 1,1 -2,4a - PONTES, Antonio Ivemar da Silva (2010)
Among the various fields of interest of the Religion Sciences, the sacred and its impact over the cultures of different peoples and ages, has been studied by many who go through that vast field. Through bibliographic studies, this project, under the lights of the Religion Sciences, intends to make an hermeneutics comparative analysis about the relationship between the Babylonian poem of Creation, Enuma Elish, and the biblical account of creation in Genesis 1. This study, which is based on Comparative Theology, seeks to analyze the influence that a culture has when interacting with others. It aims to identify some similarities and differences between these two texts from different cultures and times. It also seeks to help the reader to understand how the myth can be understood and how it can be employed in the scientific field. After analyzing the survey data, we realize that there are some elements in common between the two poems. Among them we highlight: the creation of the universe, the firmament, the stars and man. We see, therefore, that in fact, when people interact with another culture than theirs, it comes to happen a mutual influence of one people over the other.